Does Fiscal Decentralization Want to Keep Special Autonomy Funds Forever? - Finuliyah, Firdaus; Susilo, Susilo (AIBPM Publisher, 2023)
The special autonomy funds are one of the main characters in the fiscal decentralization of Papua. Papua with many problems in macroeconomics, as the key for the central government to allocate the special autonomy funds (SAF) since 2002. In law No. 21 of 2001 on special autonomy for Papua Province, states that the last year of special autonomy is 2022. Unfortunately, there is a new law that states the last year of special autonomy funds is 2041, based on the Law no. 2 of 2021. The extension of the time refers to the condition of Papua, (i) education sector; (ii) health sector; (iii) economy sector; (iv) infrastructure; and (v) good governance component. Nowadays, there are previous studies discussing the effect of the SAF on economic indicators. However, the lack of research about the factor analysis that influences central government allocate the special autonomy funds based on the financial performances in Papua. The aim of this research is to analyze the financial performance components on the opportunity to receive special autonomy funds. The analysis used the panel regression with the 28 cross sections and 20 time series. Furthermore, this study finds out the last year of the special autonomy funds, so it can help the central government to take the policies to allocate the special autonomy funds for Papua.